2014
DOI: 10.1155/2014/187979
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Patent Medicine Tongxinluo Capsule for Hypertension: A Systematic Review of Randomised Controlled Trials

Abstract: Background. This study was intended to evaluate the efficacy and safety of Tongxinluo capsule for hypertension. Search Strategy. We searched the Cochrane Central Register of Controlled Trials (CENTRAL) in the Cochrane Library, The PubMed, EMBASE, Chinese Bio-Medical Literature Database (CBM), Chinese National Knowledge Infrastructure (CNKI), Chinese Scientific Journal Database, and Wan-fang Data started from the first of database to October 28, 2013. No language restriction was applied. We included randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…TXL is a traditional Chinese medicine that was originally approved as an anti-angina drug by the CFDA in 1996. Later, the beneficial effects of its chronic use in other diseases such as hypertension (Wang J. et al, 2014 ), cardiac ventricle remodeling (Chen W. et al, 2008 ), diabetes (Chen H. et al, 2008 ; Zhang et al, 2010 ) and stroke (Wu et al, 2007 ) were validated in numerous clinical trials, where severe adverse effects were seldom reported. In other words, TXL is available as a CFDA-approved drug with an acceptable safety profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TXL is a traditional Chinese medicine that was originally approved as an anti-angina drug by the CFDA in 1996. Later, the beneficial effects of its chronic use in other diseases such as hypertension (Wang J. et al, 2014 ), cardiac ventricle remodeling (Chen W. et al, 2008 ), diabetes (Chen H. et al, 2008 ; Zhang et al, 2010 ) and stroke (Wu et al, 2007 ) were validated in numerous clinical trials, where severe adverse effects were seldom reported. In other words, TXL is available as a CFDA-approved drug with an acceptable safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…Its active constituents include peoniflorin, ginsenoside Rg1, ginsenoside Rb1, jujuboside A, jujuboside B, isoborneol and borneol (Chen et al, 2009 ). Previous studies demonstrated protective effects of TXL in a number of diseases, such as angina pectoris (Jia and Leung, 2015 ), atherosclerosis (Wu et al, 2015 ), pulmonary hypertension (Wang Y. et al, 2016 ), hypertension (Wang J. et al, 2014 ) and cerebral ischemic infarction (Cai et al, 2016 ). Although, our previous studies proved that TXL could attenuate myocardial reperfusion injury (MIRI) in an endothelial nitric oxide synthase (eNOS)-related pathway (Cheng et al, 2009 ; Li et al, 2010 ), whether TXL can protect human cardiomyocytes (HCMs) from reperfusion injury remains unknown.…”
Section: Introductionmentioning
confidence: 98%
“…Regarding clinical evidence with SRs, a small number of SRs had unclear evidence ( n = 16) [ 40 , 42 , 43 , 45 , 47 – 58 ]. Most of the SRs had a potentially positive effect ( n = 120) [ 7 , 44 , 46 , 59 – 114 ], concentrated in 5–8 score.…”
Section: Resultsmentioning
confidence: 99%
“…Tongxinluo (TXL) is a Traditional Chinese Medicine remedy that is composed of extracts from 12 kinds of Chinese medicines in exact proportion. In previous studies, its use has been shown to be beneficial in various neurological diseases [ 17 , 18 ]. Administration of TXL 24 h after cortical infarction was shown to attenuate neuronal loss, promote neurogenesis and angiogenesis in the ipsilateral thalamus, and alleviate neurological impairment after focal cortical infarction in hypertensive rats [ 17 ].…”
Section: Introductionmentioning
confidence: 99%